
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.


\(\frac{-7}{31}\) và \(\frac{6}{31}\)
\(\frac{-7}{31}<0;\frac{6}{31}>0\)
=>\(-\frac{7}{31}<\frac{6}{31}\)
\(\frac{-97}{128}\) và \(-\frac{99}{128}\)
vì \(\frac{97}{128}<\frac{99}{128}\) =>\(\frac{-97}{128}>-\frac{99}{128}\)
\(\frac37\) và \(\frac{-6}{7}\)
vì\(\frac37>0;-\frac67<0\)
=>\(\frac37>-\frac67\)

a) \(\frac{6^7}{4^3\cdot9^2}=\frac{2^7\cdot3^7}{2^6\cdot3^4}=2\cdot3^3=2\cdot27=54\)
b) \(\frac{12^3\cdot15^3}{4^3\cdot25^2\cdot9^2}=\frac{2^6\cdot3^3\cdot3^3\cdot5^3}{2^6\cdot5^4\cdot3^4}=\frac{3^2}{5}=1,8\)
c) \(\frac{2^{11}+3\cdot2^{10}}{10\cdot4^5}=\frac{2^{10}\left(2+3\right)}{2\cdot5\cdot2^{10}}=\frac{1}{2}=0,5\)
d) \(\frac{3^8\cdot2-3^6}{2\cdot17\cdot3^7}=\frac{3^6\left(3^2\cdot2-1\right)}{2\cdot17\cdot3^7}=\frac{1}{2\cdot3}=\frac{1}{6}\)

(x+1/4-1/3).(13/6-1/4)=7/46
(x+1/4-1/3).23/12=7/46
(x+1/4-1/3)=7/46:23/12
(x+1/4-1/3)=7/46.12/23
(x+1/4-1/3)=42/529
x+1/4=42/529+1/3
x+1/4=655/1587
x=655/1587-1/4
x=1033=/6348
vậy x=1033/6348

a)\(\left(4\frac{5}{37}-3\frac45+8\frac{15}{29}\right)-\left(3\frac{5}{57}-6\frac{14}{29}\right)\)
=\(4\frac{5}{37}-3\frac45+8\frac{15}{29}-3\frac{5}{37}+6\frac{14}{29}\)
=\(\left(4\frac{5}{37}-3\frac{5}{37}\right)+\left(8\frac{15}{29}+6\frac{14}{29}\right)-3\frac45\)
=\(\left\lbrack\left(4-3\right)+\left(\frac{5}{37}-\frac{5}{37}\right)\right\rbrack+\left\lbrack\left(8+6\right)+\left(\frac{15}{29}\right.\right.\)+\(\frac{14}{29})\) -\(\frac{19}{5}\)
=\(1+0+14+1-\frac{19}{5}\)
=\(15+1-\frac{19}{5}\)
=\(16-\frac{19}{5}\)
=\(\frac{80}{5}-\frac{19}{5}\)
=\(\frac{61}{5}\)

1.\(\frac{5}{7}.\frac{5}{11}+\frac{5}{7}.\frac{2}{11}-\frac{5}{7}.\frac{14}{11}\)
\(=\frac{5}{7}.\left(\frac{5}{11}+\frac{2}{11}-\frac{14}{11}\right)\)
\(=\frac{5}{7}.\frac{-7}{11}=\frac{5.\left(-7\right)}{7.11}=\frac{5.\left(-1\right)}{1.11}=\frac{-5}{11}\)
\(C=\frac{-3}{7}.\frac{5}{9}+\frac{4}{9}.\frac{-3}{7}+2\frac{3}{7}\)
\(=\frac{-3}{7}.\left(\frac{5}{9}+\frac{4}{9}\right)+2\frac{3}{7}\)
\(=\frac{-3}{7}.1+2\frac{3}{7}=\frac{-3}{7}+2\frac{3}{7}=2\)

a, -5/6 -x = 7/12 + -1/3
⇔-10/12 - 12x/12 = 7/12 + -4/12
⇒-10 - 12x = 7 - 4
⇔-12x = 7 - 4 +10
⇔-12x = 13
⇔x = -13/12
b, x+13/-15 = 1/3
⇔-(x+13)/15 = 5/15
⇒ -x - 13 = 5
⇔-x = 5 +13
⇔-x = 18
⇔x = -18
c,-15/x-1 = -3/5
⇔-75/(x-1).5 = -3.(x-1)/5.(x-1)
⇒-75 = -3x + 3
⇔3x = 3 + 75
⇔3x = 78
⇔x = 26
d, (1/2).x + -2/5 = 1/5
⇔5x/10 + -4/10 = 1/10
⇒5x - 4 = 1
⇔5x = 1 + 4
⇔5x = 5
⇔x = 1
e, (-2/3).x + 1/5 = 1/10
⇔-20x/30 + 6/30 = 3/30
⇒-20x + 6 = 3
⇔-20x = 3 - 6
⇔-20x = -3
⇔x = 3/20
f, 4/5 - (1/2).x = 1/10
⇔8/10 - 5x/10 = 1/10
⇒8 - 5x = 1
⇔-5x = 1 - 8
⇔-5x = -7
⇔x=7/5